2009
DOI: 10.1111/j.1751-0813.2009.00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Sacral osteochondrosis in two German Shepherd Dogs

Abstract: Two young adult male castrated German Shepherd Dogs were referred for evaluation of intermittent episodes of hindlimb pain. Physical examination suggested lumbosacral stenosis, and plain radiographs and computed tomography revealed lesions consistent with sacral osteochondrosis. One dog had osteochondral fragments removed surgically; the other was managed conservatively. The surgically treated dog had complete resolution of clinical signs whereas the dog managed conservatively had repeated episodes of mild pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 4 publications
3
12
3
Order By: Relevance
“…Consistent with prior publications,, , osteochondrosis was observed solely in the lumbosacral joint. Young male German Shepherds were overrepresented.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with prior publications,, , osteochondrosis was observed solely in the lumbosacral joint. Young male German Shepherds were overrepresented.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to the human experience, 20 reactive endplate changes in our population had a predilection for the lumbosacral joint (5/10: 50%), an association with degenerative disc changes (9/10: 90% with grade 4) and a tendency to affect older patients (6/10: 60% over 7 years of age).…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, in GSDs, there is an increased prevalence of congenital anomalies that can predispose affected dogs to DLSS. A separated osteochondral lesion of the dorsal endplate of S1 (or more rarely L7) that histologically resembles osteochondrosis has been reported in the GSD 3032. Ondreka et al (2013) reported a 10% incidence of sacral osteochondrosis in GSDs compared to ~6% in non-GSDs and found a moderate heritability of 0.5 in GSDs 33.…”
Section: Predisposing Factors In the Development Of Dlssmentioning
confidence: 98%
“…Both dogs were examined for evaluation of intermittent hindlimb pain 7 . Physical examination suggested lumbosacral stenosis, and plain radiographs and computed tomography showed lesions consistent with sacral osteochondrosis.…”
Section: Small Animalsmentioning
confidence: 99%